BUSINESS ANALYSIS OF ENLARGEMENT EPINEPHELUS FUSCOGUTTATUS AND CHROMILEPTES ALTIVELIS IN FLOATING NET (KJA) IN TAPIAN NAULI 1 VILLAGES TAPIAN NAULI SUBDISTRICT TAPANULI TENGAH REGENCY NORTH SUMATERA PROVINCE - Syawal Hasiansyah; Hendrik '; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study was conducted on January 2016. The purpose of this study to determine the cost of investment, gross income, net income and feasibility of fish rearing in floating net in the Tapian Nauli 1 village. The method used is a survey method to determine the respondents conducted purposive sampling.Based on the results of this research that result of financial analysis and feasibility of fish farmers as follows: 10 slots of floating net, the total investment is Rp 325. 981 .000, gross income is Rp 516.6 million, net income is Rp 201.099.500, RCR 1.64 and FRR 61.69. 8 slots of floating net, the total investment is Rp 269.130.000 , gross income is Rp 396.550.000 , net income is Rp 136.251. 500, RCR 1.52 and FRR 50.63. 5 slots of floating net, the total investment is Rp 192.691 000, gross income is Rp 281.4 million, net income is Rp 95.063.500, RCR 1.51 and FRR 49.34. Businesses of fish rearing in floating net in the Tapian Nauli 1 village has great prospect can be seen of the revenue generated, but for the business sustainability of fish farmers in the village of Tapian Nauli first confronted the problem of limited seed due to the absence of a hatchery in this village.Keywords: Tapian Nauli 1 Village, floating net, financial analysis